2021
DOI: 10.21203/rs.3.rs-473338/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking Industrial Point Sources to PFAS Contamination in Wells: Michigan Case Study

Abstract: In recent years, concern has grown over widespread environmental contamination of per- and polyfluoroalkyl substances (PFAS) in the environment and especially in drinking water. These manmade chemicals were first synthesized in the mid-20th century and contain thousands of individual species, some of which are still used today. A wide variety of industries use or have historically used PFAS in their products and processes. PFAS chemicals are recalcitrant by design and thus do not break down in the environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We identified 11 lists of Industrial Facility NAICS codes previously used by regulatory agencies and academic researchers to link PFAS contamination to facility type: the primary NAICS codes of facilities reporting TRI PFAS emissions, NAICS codes used in two academic studies that quantitatively linked facility type to PFAS contamination, , and NAICS codes from eight regulatory lists used for testing and site prioritization by state or federal agencies. ,,− To reliably identify industry facilities that are presumptive sources of PFAS contamination across the resulting 191 distinct NAICS codes, we included only 38 NAICS codes that were present on at least four lists (Table S-1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 11 lists of Industrial Facility NAICS codes previously used by regulatory agencies and academic researchers to link PFAS contamination to facility type: the primary NAICS codes of facilities reporting TRI PFAS emissions, NAICS codes used in two academic studies that quantitatively linked facility type to PFAS contamination, , and NAICS codes from eight regulatory lists used for testing and site prioritization by state or federal agencies. ,,− To reliably identify industry facilities that are presumptive sources of PFAS contamination across the resulting 191 distinct NAICS codes, we included only 38 NAICS codes that were present on at least four lists (Table S-1).…”
Section: Methodsmentioning
confidence: 99%
“…Industrial facilities are identified by North American Industry Classification System (NAICS) codes . Researchers, state environmental agencies, and the EPA have all used NAICS codes to identify facilities suspected of using PFAS, although approaches vary. ,,− Our method, described below, synthesizes previous approaches into a single set of NAICS codes that are likely sources of PFAS contamination.…”
Section: Presumptive Pfas Contaminationmentioning
confidence: 99%